1993
DOI: 10.1016/0550-3213(93)90252-k
|View full text |Cite
|
Sign up to set email alerts
|

Form factors for integrable lagrangian field theories, the sinh-Gordon model

Abstract: Using Watson's and the recursive equations satisfied by matrix elements of local operators in two-dimensional integrable models, we compute the form factors of the elementary field φ(x) and the stress-energy tensor T µν (x) of Sinh-Gordon theory. Form factors of operators with higher spin or with different asymptotic behaviour can easily be deduced from them. The value of the correlation functions are saturated by the form factors with lowest number of particle terms. This is illustrated by an application of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
286
2
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(298 citation statements)
references
References 37 publications
7
286
2
3
Order By: Relevance
“…The form factors in the sinh-Gordon model were studied by many authors [5,26,11,12]. It was shown that they as functions of the rapidities θ j factorize as follows…”
Section: Free Field Construction For Generic αmentioning
confidence: 99%
“…The form factors in the sinh-Gordon model were studied by many authors [5,26,11,12]. It was shown that they as functions of the rapidities θ j factorize as follows…”
Section: Free Field Construction For Generic αmentioning
confidence: 99%
“…The point B = 1 is known as the self-dual point. Form factors of the sinh-Gordon model were first computed in [31]. The program was thereafter extended to other operators in [32] and more recently in [33].…”
Section: The Sinh-gordon Modelmentioning
confidence: 99%
“…The Form-Factor approach has proved to be extremely successful for theories with scalar S-matrix, leading to an explicit solution of models of statistical mechanics interest such as the Ising model [1,6,14], the Yang-Lee model [15] or quantum field theories defined by a lagrangian, like the Sinh-Gordon model [7,9,13]. On the contrary, for theories with a nonscalar S-matrix the functional equations satisfied by the Form Factors are generally quite difficult to tackle and a part from the Sine-Gordon model or theories which can be brought back to it [1, 2, 4], there is presently no mathematical technique available for solving them in their full generality.…”
Section: Form Factors Of the Trace Operators Of The Sshg Modelmentioning
confidence: 99%
“…This consists in computing exactly all matrix elements of the quantum fields and then using them to obtain the spectral representations of the correlators. In addition to the rich and interesting mathematical structure presented by the Form Factors themselves (which has been investigated in a series of papers, among which [2][3][4][5][6][7][8][9][10][11][12][13], the resulting spectral series usually show a remarkable convergent behaviour which allows approximation of the correlators (or quantities related to them) within any desired accuracy [11,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%